Evaluation of Hands-Free VR Interaction Methods During a Fitts’ Task: efficiency and effectiveness - Monteiro, Pedro (2023)
Currently, it is standard to use tracked handheld controllers for interaction in immersive virtual reality (VR). However, since VR interactions are becoming more natural with hand tracking, it is important to provide hands-free alternatives for selection and system control tasks. As such, this study aims to provide an exploratory evaluation of the effectiveness and efficiency of commonly used hands-free interfaces in selection and system control tasks. Nine interaction methods were evaluated while performing a Fitts’ law task with nine advanced users of VR in a within-subject experiment. We evaluated handheld controllers as a baseline, against head gaze, eye gaze, and voice commands for pointing at the targets, and dwell time and voice commands to confirm selections. We found that using eye gaze with a 500ms dwell time proved to be the hand-free method with the highest performance, matching the handheld controllers and being preferred by users. The evaluation also showed that using a multimodal approach to selection, especially using the voice, decreases performance, but increases effectiveness. Moreover, we verified that Fitts’ law can be applied to hands-free methods, but its usage is limited when the methods have very short travel times. We then suggest selections per minute as a more robust comparative performance metric. Further studies should expand the audience and interaction tasks and focus on the confirmatory method of selection.